As tessituras da violência na ficção de Dalton Trevisan e Antonio Carlos Viana - Lima, Raquel Pereira de (2014)
Based on the readings of Antonio Carlos Viana and Dalton Trevisan, it was noticed the occurrence of similar situations which include violence directed at all levels of society, be it sexual or social. Both authors produce works that peculiarly exhibit to the readers violent relationships in an unusual manner, leading them to see beyond what is written in every detail of the author's works. Founded on the thematic of violence, we selected Viana and Trevisan's short stories in order to discover the structure created from the writing and style of both writers. To do so, we chose the following short stories: “A culpada”, “O grande deflorador” and “Ezequiel”, by Trevisan, published respectively in Violetas e Pavões (2009), Chorinho Brejeiro (1981) and Duzentos ladrões (2008); by Viana, “Barba de arame”, “Das Dores” and “Olhos de fogo” in Aberto está o inferno (2004) and O meio do mundo e outros contos (1993). Furthermore, aiming to understand building style processes and the prevalent thematic, we opted for theories regarding the short story genre, such as of: Moisés (2012) and Cortázar (1993); concerning violence we studied: Nilo Odalia (2004), Yves Michaud (2001), Morais (1983), Arendt (1985), Lia Zanotta Machado (1998, 1999, 2000, 2001, 2006), Rita Laura Segato (1993, 1998, 2003, 2004, 2006), and other complementary texts.